Mémoire présenté au Comité permanent des langues officielles de la Chambre des communes au sujet du projet de loi C-13 : Loi modifiant la Loi sur les langues officielles, édictant la Loi sur l’usage du français au sein des entreprises privées de compétence fédérale et apportant des modifications connexes à d’autres lois - O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
Le présent mémoire est axé sur le premier objectif — les modifications apportées à la LLO par le projet de loi C-13 —, car il s’agit du sujet sur lequel j’ai développé le plus de connaissances à titre d’attachée de recherche pour le Réseau de recherche sur les communautés québécoises d’expression anglaise (QUESCREN)

Stories of a Small “Shtetl” : Jewish History in Drummondville - Miller, Julie (2022)

Newsletter: August 2022 : Independence Special Edition : Volume 25.1 - Jamaica Association of Montreal (JAM) (2022)

Aller au-delà des solitudes : Contributions, pratiques linguistiques et identités des Québécois anglophones - O'Donnell, Lorraine; Donovan, Patrick (2022)

Money Raised for La Rose des Vents de Drummond and a Successful First Edition of the “History and Music” Concert Series - Centre for Access to Services in English (CASE) (2022)

Nos pionniers locaux! : Un balado sur la contribution et la collaboration entre les francophones et les anglophones à la société québécoise en Outaouais d’hier à aujourd’hui. - Nivischiuk, Jeanne (2022)

Our Local Pioneers! : A Podcast on the Collaboration between Francophones and Anglophones in the Outaouais and their Contributions to Quebec Society, from Yesterday to Today - Nivischiuk, Jeanne (2022)

The Best-Treated Minority in the World : Historical and Discursive Analysis of a Cliché - Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
Politicians, polemicists, and others have long referred to Quebec’s Englishspeaking community as the “best-treated minority in the world.”1 This loaded phrase has also been used to describe other minorities: French speakers within Canada as a whole, Indigenous peoples in Canada, and religious groups and minorities in many European and colonial contexts. Through a historical overview and discourse analysis, this paper traces how the phrase has been used and abused, justified, and criticized over time. The particular focus is the Quebec context. There, we see a shift from a largely consensual use of the phrase across all language groups to one that becomes increasingly divisive and problematic from the 1980s on. This shift parallels the English-speaking community’s evolving sense of itself as a minority in decline.
Keywords: Official Language Minority Community (OLMC)

The Tourist Offer of the Whiteley Museum and its Surrounding Area on the Lower North Shore : A Quality Improvement Report - Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
This report analyzes the tourist offer in the eastern part of Quebec’s Lower North Shore, particularly the municipality of Bonne-Espérance, a region where English speakers make up the majority of the population. It focuses specifically on an institution in one of these municipalities, the Whiteley Museum. The report provides the authors’ suggestions to improve tourism development as a means to diversify the economy, potentially help reverse demographic decline, and build community vitality.

Resolution 2022-02 : Request to Maintain Race, Religion, and Culture as Central Themes in the Proposed Citizenship Course - Quebec Federation of Home and School Associations (QFHSA) (2022)